Solder paste and preparation and use method thereof

By using specific components of flux and nanotitanium dioxide powder and tin-based alloy powder in small-size LED packaging, the problem of dry deterioration of solder paste at room temperature is solved, and the service life and packaging performance of the solder paste are improved.

CN119857963APending Publication Date: 2025-04-22JIANGXI MTC VISUAL DISPLAY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510235282.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In small-size LED packages, conventional fluxes and oxides on the surface of tin-based alloy powder are prone to react at room temperature, causing the solder paste to deteriorate, reducing its service life and packaging performance.

Method used

A new solder paste is prepared by combining nanotitanium dioxide powder and tin-based alloy powder of specific components using fluxes of specific components, including lactic acid-glycolic acid copolymer and phthalic acid as active agents. The flux acts as an activating effect at different temperatures, reduces the use of resin film forming agent, and improves the mechanical properties and electrical reliability of solder paste.

Benefits of technology

By reducing the reaction speed of flux and tin-based alloy powder, the service life of solder paste is extended, the performance and reliability of LED devices are improved, and the service life of solder paste is significantly extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005292589750000071
    Figure BDA0005292589750000071
  • Figure BDA0005292589750000081
    Figure BDA0005292589750000081
  • Figure BDA0005292589750000082
    Figure BDA0005292589750000082
Patent Text Reader

Abstract

The invention discloses solder paste as well as a preparation method and a use method thereof. The solder paste comprises the following components in parts by mass: 80-110 parts of tin-based alloy powder, 0.8-1.5 parts of nano titanium dioxide powder and 15-30 parts of soldering flux, the soldering flux comprises the following components in percentage by mass: 10%-20% of a resin film-forming agent, 8%-15% of an active agent, 1%-8% of a thixotropic agent, 5%-10% of an auxiliary agent and the balance of a solvent. Wherein the active agent is prepared from a lactic acid-glycollic acid copolymer and phthalic acid. According to the invention, the solder paste packaging performance and the service life in small-size LED packaging can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of welding technology, and in particular to a solder paste and a preparation and use method thereof. Background Art

[0002] Solder paste is an extremely important and indispensable material in LED packaging. Solder paste is a paste with certain rheological properties made by mixing solder alloy powder and flux. At room temperature, the electrodes of the LED light-emitting chip are connected to the pads of the circuit board through solder paste, and then reflow soldering is performed. As the solvent and some additives in the flux evaporate, the solder alloy powder melts and cools and solidifies, the LED light-emitting chip and the circuit board are fixedly connected. The quality of welding directly affects the quality of LED devices.

[0003] In order to improve the quality of welding, it is usually necessary to use a flux containing many active components to remove oxides on the surface of the solder alloy powder, thereby increasing the spreading rate. Accordingly, at room temperature, the flux and the oxides on the surface of the solder alloy powder are prone to react, causing the solder paste to dry out and deteriorate, or even become scrapped and ineffective. Especially in small-sized LED packaging, it is necessary to use solder alloy powders with smaller particle sizes, which have more surface oxides. The use of conventional flux will aggravate the drying and deterioration of the solder paste at room temperature and reduce the service life of the solder paste. In addition, the performance reliability requirements of small-particle solder alloy powders after solder paste packaging are also further increased. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a solder paste and a preparation and use method thereof, so as to improve the packaging performance and service life of the solder paste in small-size LED packaging.

[0005] In order to solve the above problems, the present invention discloses a solder paste, which comprises the following components by mass: 80 to 110 parts of tin-based alloy powder, 0.8 to 1.5 parts of nano titanium dioxide powder, and 15 to 30 parts of flux;

[0006] The soldering flux comprises the following components by mass percentage: 10% to 20% of a resin film former, 8% to 15% of an active agent, 1% to 8% of a thixotropic agent, 5% to 10% of an auxiliary agent, and the balance being a solvent; wherein the active agent is composed of a lactic acid-glycolic acid copolymer and phthalic acid.

[0007] As an improvement of the above technical solution, the mass ratio of the lactic acid-glycolic acid copolymer to phthalic acid is 1:(0.4-1).

[0008] As an improvement of the above technical solution, the resin film-forming agent is one or more of hydrogenated rosin resin, polymerized rosin, disproportionated rosin resin, acid-modified rosin, acrylic resin, and phenolic resin;

[0009] The thixotropic agent is one or more of dehydrated castor oil fatty acid, ricinoleic acid, polymerized dehydrated castor oil, hydrogenated castor oil, modified hydrogenated castor oil, and ethylene bisstearamide;

[0010] The auxiliary agent includes one or more of a surfactant, a defoamer, and an antioxidant; the surfactant is one or more of GE-511, EB-9, AP-8, OP-10, FC-134, and FT-134; the defoamer is one or more of mineral oil, polyoxyethylene glyceryl ether, polyoxypropyl glyceryl ether, polyoxypropyl polyoxyethyl glyceryl ether, methyl silicone oil, and dimethyl silicone oil; the antioxidant is one or more of triphenyl phosphate, triphenyl phosphite, butylated hydroxyanisole, and butylated hydroxytoluene;

[0011] The solvent is one or more of dipropylene glycol methyl ether, hexylene glycol, tetrahydrofurfuryl alcohol, butyl acetate, benzyl alcohol, nitromethane, glycerol, propylene glycol, ethylene glycol, ethanol, methanol, diethylene glycol dibutyl ether, and diethylene glycol monomethyl ether.

[0012] As an improvement of the above technical solution, the tin-based alloy powder includes the following components by mass percentage: Ag 0.5%-1%, Cu 0.2%-0.6%, Ni 0.05%-0.08%, Bi 0.005%-0.02%, Sb 0.005%-0.02%, and the balance is Sn.

[0013] As an improvement of the above technical solution, the D50 of the nano titanium dioxide powder is 10nm to 120nm;

[0014] The tin-based alloy powder has a D50 of 8 μm to 12 μm and a specific surface area of ​​1 m 2 / cm 3 ~1.5m 2 / cm 3 .

[0015] Correspondingly, the present invention also discloses a method for preparing solder paste, which is used to prepare the above-mentioned solder paste, comprising the following steps: mixing nano titanium dioxide powder and flux in proportion, stirring at a speed of 500r / min to 900r / min for 120s to 180s, then adding tin-based alloy powder and mixing, and stirring at a speed of 500r / min to 900r / min for 120s to 180s.

[0016] As an improvement of the above technical solution, the preparation method of the flux includes the following steps: mixing the solvent, resin film-forming agent and thixotropic agent in proportion, heating to 170°C to 190°C and stirring evenly, cooling to 60°C to 80°C, adding the activator and auxiliary agent in sequence, stirring to dissolve, and cooling to room temperature to obtain the flux.

[0017] Correspondingly, the present invention also discloses a method for using solder paste, comprising the following steps:

[0018] (1) taking the above solder paste and stirring it evenly to obtain a first solder, and applying the first solder to the area to be soldered at 20° C. to 25° C.;

[0019] (2) After an interval of 4 to 6 hours, the viscosity of the first solder is detected. If the viscosity of the first solder is greater than 240 Pa·s to 260 Pa·s, a preset amount of the above-mentioned solder paste is added and stirred evenly to obtain a second solder, and the second solder is applied to the area to be soldered at 20° C. to 25° C.;

[0020] (3) Repeat for 36 to 42 hours and then recycle and scrap.

[0021] As an improvement of the above technical solution, the viscosity of the solder paste is 160 Pa·s to 200 Pa·s.

[0022] As an improvement of the above technical solution, in step (1), the mass ratio of the tin-based alloy powder and the flux of the solder paste is 1:(0.15-0.2);

[0023] In step (2), the mass ratio of the tin-based alloy powder and the soldering flux added to the solder paste is 1:(0.2-0.35).

[0024] The implementation of the present invention has the following beneficial effects:

[0025] 1. The present invention uses a flux of a specific component in a solder paste of a small-particle tin-based alloy powder, which is beneficial to reduce the reaction rate of the flux and the tin-based alloy powder at room temperature and improve the service life of the solder paste. The use of an activator of a specific component can reduce the amount of resin film-forming agent used while ensuring the activity of the flux, reduce the residue after welding, and improve the performance of the LED device after welding.

[0026] 2. The present invention can effectively improve the mechanical properties of solder paste and improve electrical reliability by selecting tin-based alloy powder with specific ingredients and mixing it with nano titanium dioxide powder and flux in a specific ratio.

[0027] 3. During the use of the solder paste, the present invention adds a preset amount of solder paste at a preset time, which significantly extends the service life of the solder paste compared to directly scrapping it after 8 hours of use. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in further detail below.

[0029] The present invention provides a solder paste, which comprises the following components by mass: 80 to 110 parts of tin-based alloy powder, 0.8 to 1.5 parts of nano titanium dioxide powder, and 15 to 30 parts of flux;

[0030] The soldering flux comprises the following components by mass percentage: 10% to 20% of a resin film former, 8% to 15% of an active agent, 1% to 8% of a thixotropic agent, 5% to 10% of an auxiliary agent, and the balance being a solvent; wherein the active agent is composed of a lactic acid-glycolic acid copolymer and phthalic acid.

[0031] The tin-based alloy powder used in small-size LED packaging is finer than that of traditional solder paste, and the area of ​​the oxide film of the tin-based alloy powder is larger, which is more easily corroded by active substances. The present invention obtains an active agent by compounding lactic acid-glycolic acid copolymer and phthalic acid. The lactic acid-glycolic acid copolymer degrades at high temperature to generate lactic acid and glycolic acid. The boiling point of lactic acid is 122°C, and it is easily soluble in ethanol, ether, etc. The melting temperature of glycolic acid is 75°C to 80°C, and the boiling point under normal pressure is 112°C, and it is easily soluble in methanol, ethanol, etc. Phthalic acid is soluble in organic solvents such as methanol and ethanol, has strong activity and weak acidity, and has a melting temperature of 227°C and a boiling point of 230°C. The lactic acid-glycolic acid copolymer and phthalic acid are selected for compounding, and the difference in melting temperature enables the flux to play an activation role at different temperatures, and when the temperature rises to the melting point of the tin-based alloy powder, the lactic acid-glycolic acid copolymer and phthalic acid can be decomposed without residue. The soldering flux provided by the present invention can make the tin-based alloy powder maintain stable performance at room temperature and can contact with the soldering pad at high temperature and smoothly wet, so as to achieve the purpose of soldering. In addition, through the compounding of the activator, the addition amount of the resin film-forming agent can be controlled within 10% to 20%, and the addition amount of the resin film-forming agent can be reduced, thereby reducing the post-soldering residue of the solder paste and reducing the surface insulation resistance.

[0032] In a preferred embodiment, the mass ratio of the lactic acid glycolic acid copolymer to phthalic acid is 1:(0.4-1), exemplified by 1:0.5, 1:0.6, 1:0.7, 1:0.8 or 1:0.9, but not limited thereto. If the mass ratio of the lactic acid glycolic acid copolymer is too large, the activity of the soldering flux is not high; if the mass ratio of phthalic acid is too large, it will cause corrosion to the circuit board.

[0033] Optionally, the resin film-forming agent is one or more of hydrogenated rosin resin, polymerized rosin, disproportionated rosin resin, acid-modified rosin, acrylic resin, and phenolic resin;

[0034] The thixotropic agent is one or more of dehydrated castor oil fatty acid, ricinoleic acid, polymerized dehydrated castor oil, dodecyl hydroxystearic acid, oleamide, hydrogenated castor oil, modified hydrogenated castor oil, and ethylene bisstearamide;

[0035] The auxiliary agent includes one or more of a surfactant, a defoamer, and an antioxidant; the surfactant is one or more of GE-511, EB-9, AP-8, OP-10, FC-134, and FT-134; the defoamer is one or more of mineral oil, polyoxyethylene glyceryl ether, polyoxypropyl glyceryl ether, polyoxypropyl polyoxyethyl glyceryl ether, methyl silicone oil, and dimethyl silicone oil; the antioxidant is one or more of triphenyl phosphate, triphenyl phosphite, butylated hydroxyanisole, and butylated hydroxytoluene;

[0036] The solvent is one or more of dipropylene glycol methyl ether, hexylene glycol, tetrahydrofurfuryl alcohol, butyl acetate, benzyl alcohol, nitromethane, glycerol, propylene glycol, ethylene glycol, ethanol, methanol, diethylene glycol dibutyl ether, and diethylene glycol monomethyl ether.

[0037] The preparation method of the soldering flux comprises the following steps: mixing a solvent, a resin film-forming agent and a thixotropic agent in proportion, heating to 170° C. to 190° C. and stirring evenly, cooling to 60° C. to 80° C., adding an activator and an auxiliary agent in sequence, stirring to dissolve, and cooling to room temperature to obtain the soldering flux.

[0038] In a preferred embodiment, the tin-based alloy powder comprises the following components by mass percentage: Ag 0.5% to 1%, Cu 0.2% to 0.6%, Ni 0.05% to 0.08%, Bi 0.005% to 0.02%, Sb 0.005% to 0.02%, and the balance is Sn. Compared with the existing tin-based alloy powder, the tin-based alloy powder of the present invention is mainly composed of SnAgCu alloy, and through the adjustment of multiple trace elements, the grains are refined, the strength, hardness and heat resistance of the alloy are improved, thereby improving the stability and ductility of the solder paste and meeting the requirements of small-size packaging.

[0039] In a preferred embodiment, the D50 of the nano titanium dioxide powder is 10nm to 120nm, exemplarily 20nm, 40nm, 50nm, 60nm, 80nm or 100nm, but not limited thereto. Nano titanium dioxide powder can improve the mechanical properties of solder paste without affecting the melting point of solder paste. If the D50 of the nano titanium dioxide powder is less than 10nm, it is difficult to effectively improve the mechanical properties of the solder paste; if the D50 of the nano titanium dioxide powder is greater than 120nm, it may cause agglomeration of the nano titanium dioxide powder.

[0040] In a preferred embodiment, the D50 of the tin-based alloy powder is 8 μm to 12 μm, exemplarily 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm or 11 μm, but not limited thereto, and the specific surface area is 1 m 2 / cm 3 ~1.5m 2 / cm3 , exemplarily 1.1m 2 / cm 3 、1.15m 2 / cm 3 , 1.2m 2 / cm 3 、1.25m 2 / cm 3 、1.3m 2 / cm 3 or 1.4m 2 / cm 3 , but not limited to this.

[0041] The preparation method of the solder paste comprises the following steps: mixing nano titanium dioxide powder and flux according to proportion, stirring at a speed of 500r / min-900r / min for 120s-180s, then adding tin-based alloy powder and mixing, and stirring at a speed of 500r / min-900r / min for 120s-180s to obtain the solder paste.

[0042] Accordingly, the present invention provides a method for using solder paste, comprising the following steps:

[0043] S1. Take the above solder paste and stir it evenly to obtain the first solder, and apply the first solder to the area to be soldered at 20°C to 25°C. The viscosity of the solder paste is 160Pa·s to 200Pa·s, and is exemplarily 165Pa·s, 170Pa·s, 175Pa·s, 180Pa·s, 190Pa·s or 195Pa·s, but is not limited thereto. It is understandable that after applying the first solder to the area to be soldered of the circuit board, the LED light-emitting chip is placed on the first solder, and the LED light-emitting chip is fixedly connected to the circuit board by reflow soldering.

[0044] S2. After an interval of 4h to 6h, the viscosity of the first solder is detected. If the viscosity of the first solder is greater than 240Pa·s to 260Pa·s, a preset amount of the above-mentioned solder paste is added and stirred evenly to obtain a second solder, and the second solder is applied to the area to be welded at 20℃ to 25℃.

[0045] In a preferred embodiment, compared with the solder paste taken in step (1), the mass ratio of the solder flux of the solder paste added in step (2) is higher, that is, more solder flux needs to be added. More preferably, in step (1), the mass ratio of the tin-based alloy powder and the solder flux of the solder paste taken is 1:(0.15-0.2), exemplarily 1:0.155, 1:0.16, 1:0.165, 1:0.17, 1:0.18 or 1:0.19, but not limited thereto; in step (2), the mass ratio of the tin-based alloy powder and the solder flux of the solder paste added is 1:(0.2-0.35), exemplarily 1:0.25, 1:0.28, 1:0.3, 1:0.31, 1:0.32 or 1:0.34, but not limited thereto.

[0046] S3. Repeat until 36h to 42h and then recycle and scrap.

[0047] The use method of the solder paste provided by the present invention can extend the service life of the solder paste. Conventionally, after the solder paste is prepared, it is used for welding and solidifying, and the online time is generally 8 hours. During use, the solder paste dries and deteriorates at room temperature, that is, the solder paste needs to be scrapped after 8 hours of use. However, by using the solder paste and the use method provided by the present invention, the viscosity of the solder is reduced by re-adding the solder paste to the solder after a period of use, and the re-mixed solder can continue to be used for welding and solidifying, ensuring the welding performance of the material while extending the service life.

[0048] The present invention will be further described below with specific embodiments:

[0049] Example 1

[0050] The present embodiment provides a solder paste, which includes the following components by mass: 90 parts of tin-based alloy powder, 1.2 parts of nano titanium dioxide powder, and 17 parts of flux.

[0051] The tin-based alloy powder is SAC305 alloy powder, with a D50 of 10 μm and a specific surface area of ​​1.2 m 2 / cm 3 .

[0052] The D50 of nano titanium dioxide powder is 200nm.

[0053] The soldering flux comprises the following components by mass percentage: 15% of disproportionated rosin resin, 12% of activator, 6% of hydrogenated castor oil, 5% of OP-10, and the balance is solvent; wherein the activator is composed of lactic acid glycolic acid copolymer and phthalic acid, and the mass ratio of lactic acid glycolic acid copolymer to phthalic acid is 1:0.3.

[0054] Example 2

[0055] This embodiment provides a solder paste, which is different from the embodiment 1 in that the mass ratio of the lactic acid glycolic acid copolymer to phthalic acid in the active agent is 1:0.8. The rest is the same as the embodiment 1.

[0056] Example 3

[0057] This embodiment provides a solder paste, which differs from the embodiment 2 in that the tin-based alloy powder comprises the following components by mass percentage: Ag 0.8%, Cu 0.4%, Ni 0.06%, Bi 0.008%, Sb 0.006%, and the balance is Sn. The rest is the same as the embodiment 2.

[0058] Example 4

[0059] This embodiment provides a solder paste, which is different from the embodiment 3 in that the D50 of the nano titanium dioxide powder is 80 nm. The rest is the same as the embodiment 3.

[0060] Example 5

[0061] This embodiment provides a solder paste, which is different from the embodiment 4 in that the solder paste comprises the following components by mass: 90 parts of tin-based alloy powder, 1.2 parts of nano titanium dioxide powder, and 20 parts of flux. The rest is the same as the embodiment 4.

[0062] Example 6

[0063] This embodiment provides a method for using solder paste, comprising the following steps:

[0064] S100, taking the solder paste provided in Example 4 and stirring it evenly to obtain a first solder, and applying the first solder to the area to be soldered at 20° C. to 25° C.;

[0065] S200, detecting the viscosity of the first solder every 6 hours. If the viscosity of the first solder is greater than 250 Pa·s, adding the solder paste provided in Example 4 and stirring evenly to obtain a second solder, and applying the second solder to the area to be soldered at 20°C to 25°C.

[0066] S300, repeat until 36 hours and then recycle and scrap.

[0067] Example 7

[0068] This embodiment provides a method for using solder paste, comprising the following steps:

[0069] S100, taking the solder paste provided in Example 4 and stirring it evenly to obtain a first solder, and applying the first solder to the area to be soldered at 20° C. to 25° C.;

[0070] S200, detecting the viscosity of the first solder every 6 hours. If the viscosity of the first solder is greater than 250 Pa·s, adding the solder paste provided in Example 5 and stirring evenly to obtain a second solder, and applying the second solder to the area to be soldered at 20°C to 25°C.

[0071] S300, repeat until 36 hours and then recycle and scrap.

[0072] According to GB / T 31474-2015 and IPCTM650, the solder pastes provided in Examples 1 to 5 were tested for performance, and according to IPC-A-610, the LED devices encapsulated by the methods of Examples 6 and 7 were tested for performance. The specific test results are as follows:

[0073] Table 1 Solder paste performance test

[0074]

[0075]

[0076] Table 2 LED device performance test

[0077]

[0078] The above is a preferred embodiment of the invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the invention. These improvements and modifications are also considered to be within the scope of protection of the invention.

Claims

1. A solder paste, characterized in that: The components include the following by mass: 80 to 110 parts of tin-based alloy powder, 0.8 to 1.5 parts of nano titanium dioxide powder, and 15 to 30 parts of flux; The soldering flux comprises the following components by mass percentage: 10% to 20% of a resin film former, 8% to 15% of an active agent, 1% to 8% of a thixotropic agent, 5% to 10% of an auxiliary agent, and the balance being a solvent; wherein the active agent is composed of a lactic acid-glycolic acid copolymer and phthalic acid.

2. The solder paste according to claim 1, characterized in that The mass ratio of the lactic acid-glycolic acid copolymer to phthalic acid is 1:(0.4-1).

3. The solder paste according to claim 1, characterized in that The resin film-forming agent is one or more of hydrogenated rosin resin, polymerized rosin, disproportionated rosin resin, acid-modified rosin, acrylic resin, and phenolic resin; The thixotropic agent is one or more of dehydrated castor oil fatty acid, ricinoleic acid, polymerized dehydrated castor oil, hydrogenated castor oil, modified hydrogenated castor oil, and ethylene bisstearamide; The auxiliary agent includes one or more of a surfactant, a defoamer, and an antioxidant; the surfactant is one or more of GE-511, EB-9, AP-8, OP-10, FC-134, and FT-134; the defoamer is one or more of mineral oil, polyoxyethylene glyceryl ether, polyoxypropyl glyceryl ether, polyoxypropyl polyoxyethyl glyceryl ether, methyl silicone oil, and dimethyl silicone oil; the antioxidant is one or more of triphenyl phosphate, triphenyl phosphite, butylated hydroxyanisole, and butylated hydroxytoluene; The solvent is one or more of dipropylene glycol methyl ether, hexylene glycol, tetrahydrofurfuryl alcohol, butyl acetate, benzyl alcohol, nitromethane, glycerol, propylene glycol, ethylene glycol, ethanol, methanol, diethylene glycol dibutyl ether, and diethylene glycol monomethyl ether.

4. The solder paste according to claim 1, characterized in that The tin-based alloy powder comprises the following components by mass percentage: Ag 0.5%-1%, Cu 0.2%-0.6%, Ni 0.05%-0.08%, Bi 0.005%-0.02%, Sb 0.005%-0.02%, and the balance is Sn.

5. The solder paste according to claim 1, characterized in that: The D50 of the nano titanium dioxide powder is 10nm to 120nm; The tin-based alloy powder has a D50 of 8 μm to 12 μm and a specific surface area of ​​1 m 2 / cm 3 ~1.5m 2 / cm 3 .

6. A method for preparing solder paste, characterized in that: The method for preparing the solder paste as claimed in any one of claims 1 to 5 comprises the following steps: mixing nano titanium dioxide powder and flux in proportion, stirring at a speed of 500 r / min to 900 r / min for 120 s to 180 s, then adding tin-based alloy powder and mixing, and stirring at a speed of 500 r / min to 900 r / min for 120 s to 180 s.

7. The method for preparing solder paste according to claim 6, characterized in that: The preparation method of the soldering flux comprises the following steps: mixing a solvent, a resin film-forming agent and a thixotropic agent in proportion, heating to 170° C. to 190° C. and stirring evenly, cooling to 60° C. to 80° C., adding an activator and an auxiliary agent in sequence, stirring to dissolve, and cooling to room temperature to obtain the soldering flux.

8. A method for using solder paste, characterized in that: The following steps are involved: (1) taking the solder paste as described in any one of claims 1 to 5 and stirring it evenly to obtain a first solder, and applying the first solder to the area to be soldered at 20° C. to 25° C.; (2) After an interval of 4 to 6 hours, the viscosity of the first solder is detected. If the viscosity of the first solder is greater than 240 Pa·s to 260 Pa·s, a preset amount of the solder paste according to any one of claims 1 to 5 is added and stirred evenly to obtain a second solder, and the second solder is applied to the area to be soldered at 20° C. to 25° C.; (3) Repeat for 36 to 42 hours and then recycle and scrap.

9. The method for using solder paste according to claim 8, characterized in that: The viscosity of the solder paste is 160 Pa·s to 200 Pa·s.

10. The method for using solder paste according to claim 8, characterized in that: In step (1), the mass ratio of the tin-based alloy powder and the flux of the solder paste is 1:(0.15-0.2); In step (2), the mass ratio of the tin-based alloy powder and the soldering flux added to the solder paste is 1:(0.2-0.35).